Reconceptualization of Population Data as a Human Right under Indonesian Positive Law - Ana Aniza Karunia; Mohammad Jamin; Adriana Grahani Firdausy (PT FORMOSA CENDEKIA GLOBAL, 2026)
The rapid digitalization of public services has significantly increased the use of population data as a key instrument in governance, public services, and development planning. However, this expansion also raises serious concerns regarding the legal status and protection of such data. This study aims to analyze the nature of population data. Using a normative legal research method wih statutory, conceptual, and historical approaches, this research relies on secondary data obtained through documents study. The findings show that population data constitute personal data inherent to individuals, derived from life events, and closely related to identity, privacy, and human dignity. At the same time, it is managed by the state and utilized for public interests, placing it in a sui generis position, both personal and public in nature. The increasing economic utilization of population data further intensifies the tension between public interest and privacy protection. This study concludes that strengthening legal foundations, harmonizing regulations, and developing a comprehensive data protection system are essential to ensure that the use of population data remains aligned with the protection of human rights, particularly the right to privacy.